+0  
 
0
72
2
avatar

Please help with this problem!

Guest Oct 10, 2018
 #1
avatar+92430 
+1

( 4^0)^6  = 4^(0 * 6)  = 4^0    False

 

3^8  / 3 ^(-2)  =  3^(8 - (- 2 ) )  = 3^10    True

 

2^(-5)  * 2^(3)  = 2^( -5 + 3)  = 2^(-2)   =  1 /2^2     True

 

6^4 * 3^4  =  (2 * 3)^4 * 3^4  = 2^4 * 3^4 * 3^4  = 16 * 3^(8)   False

 

 

 

cool cool cool

CPhill  Oct 10, 2018
edited by CPhill  Oct 10, 2018
 #2
avatar+464 
+1

Yep it is 

False for no 1

True for no 2

True for no 3

False for no 4

 

Ask me later if you want me to show work

shreyas1  Oct 10, 2018

26 Online Users

avatar
avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.